Be Fearless with Fenty: A Campaign Exploring Fenty Beauty Inclusive Beauty Concept - Kristi Candi; Dwi Setiawan; Bernadeth Febyola Linando (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This paper aims to explore what kind of campaign that can promote and how the campaign can represent inclusive beauty concepts. The issue of inclusivity has been important since society is still affected by the traditional beauty standards which result in the lack of darker foundation shades and higher sale of whitening products. This paper portrays Fenty Beauty’s inclusivity beauty concept which is applied in a social media campaign and a mockup website that is aligned with the brand's tone-of-voices and target audience while using brand awareness and content marketing strategies. The work is written in the form of a social media campaign that shows encouragement towards Indonesian women to be confident in their own skin using the tone-of-voices of confident, informal, and inclusive. It also contains engaging contents to spread awareness and increase engagement of the audiences to be involved in the campaign.